2010
DOI: 10.1002/asia.201000674
|View full text |Cite
|
Sign up to set email alerts
|

A Rational Repeating Template Method for Synthesis of 2 D Hexagonally Ordered Mesoporous Precious Metals

Abstract: A repeating template method is presented for the synthesis of mesoporous metals with 2D hexagonal mesostructures. First, a silica replica (i.e., silica nanorods arranged periodically) is prepared by using 2D hexagonally ordered mesoporous carbon as the template. After that, the obtained silica replica is used as the second template for the preparation of mesoporous ruthenium. After the ruthenium species are introduced into the silica replica, the ruthenium species are then reduced by a vapor-infiltration metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Among the periodic table of elements, metals of silver, nickel, copper, palladium, ruthenium, titanium, and platinum have been intensively investigated for their porous foam. For example, Walsh et al used dextran as a sacrificial template to fabricate silver sponges, Yamauchi and coworkers prepared mesoporous nickel by an electroless deposition method in the presence of lyotropic liquid crystals, and Kuroda et al reported 2D hexagonally ordered mesoporous metals (Ru, Pt, or Pd) by dissolving silica replica [9][10][11]. In addition to these methods, the combustion technology is a general method to synthesize various porous metals and oxides [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the periodic table of elements, metals of silver, nickel, copper, palladium, ruthenium, titanium, and platinum have been intensively investigated for their porous foam. For example, Walsh et al used dextran as a sacrificial template to fabricate silver sponges, Yamauchi and coworkers prepared mesoporous nickel by an electroless deposition method in the presence of lyotropic liquid crystals, and Kuroda et al reported 2D hexagonally ordered mesoporous metals (Ru, Pt, or Pd) by dissolving silica replica [9][10][11]. In addition to these methods, the combustion technology is a general method to synthesize various porous metals and oxides [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the periodic table of elements, metals of silver, nickel, copper, palladium, ruthenium, titanium, and platinum have been intensively investigated for their porous foam. For example, Walsh et al used dextran as a sacrificial template to fabricate silver sponges, Yamauchi and co-workers prepared mesoporous nickel by an electroless deposition method in the presence of lyotropic liquid crystals, and Kuroda et al reported 2D hexagonally ordered mesoporous metals (Ru, Pt, or Pd) by dissolving silica replica [ 9 - 11 ]. In addition to these methods, the combustion technology is a general method to synthesize various porous metals and oxides [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%